BUSINESS – MARKET AS A MARKET WITH NO PROSPECTS - Lidia I. Kochurova (Plekhanov Russian University of Economics, 2018)
High-level technologies were brought to our planet in the 20th and early 21st century. In the technical aspect mankind has made a great step forward while science about market is still underdeveloped. Thus, instead of the developed form of market relations mankind has reached business – market, the most perverted form of market in human history. The article proved that business – market could be dangerous for people. It will never become a model for social and economic structure of state. Arising of business – market is connected with the fact that countries could not develop a controlled market as there is no science. Business – market is a consequence of the fact that science cannot see a developed form of market. It is business – market that has pushed world economy to the global crisis. If we speak about the essence of the crisis, it was initially provoked by the US. The first precondition of the global crisis was stock exchanges. While stock exchange was working within economic space of countries, it had a positive impact, but as soon as it overstepped state limits it gained a negative impact. Principle elements of the national market are not stock exchanges, but goods, money and value. Commercialization was the second precondition of the crisis. Commercial banks are harmful for any state. As the bank becomes state-owned the ground for enrichment of crisis culprit will disappear. The non-governmental structure of the Federal Reserve System controls finances of the world. This global money-lender is controlled by no one. A crisis is a response to the incorrect pursuing of economy. All countries of the world need economic activity coordinated with economic laws. It is necessary to restructure our state into the developed form of market and then Russia will be able to overcome the crisis and build a controlled market.